Natural Compounds for the Treatment of Acute Pancreatitis: Novel Anti-Inflammatory Therapies - Wenkai Jiang; Xiao Li; Yi Zhang; Wence Zhou (Biomolecules)
Acute pancreatitis remains a serious public health problem, and the burden of acute pancreatitis is increasing. With significant morbidity and serious complications, appropriate and effective therapies are critical. Great progress has been made in understanding the pathophysiology of acute pancreatitis over the past two decades. However, specific drugs targeting key molecules and pathways involved in acute pancreatitis still require further study. Natural compounds extracted from plants have a variety of biological activities and can inhibit inflammation and oxidative stress in acute pancreatitis by blocking several signaling pathways, such as the nuclear factor kappa-B and mitogen-activated protein kinase pathways. In this article, we review the therapeutic effects of various types of phytochemicals on acute pancreatitis and discuss the mechanism of action of these natural compounds in acute pancreatitis, aiming to provide clearer insights into the treatment of acute pancreatitis.